2018
DOI: 10.37358/rc.18.6.6369
|View full text |Cite
|
Sign up to set email alerts
|

Meningiomas Related to the Chernobyl Irradiation Disaster in North-Eastern Romania Between 1990 and 2015

Abstract: Even if meningiomas are the most common radio-induced tumors that occur in the adult population, the epidemiology of these types of tumors after Chernobyl nuclear accident, is still unclear. This paper aims to determine the tumoral behavior of intracranial meningiomas in North-Eastern Romania, affected by the radioactive cloud from Chernobyl nuclear accident , over a period of 25 years, namely between 1990 and 2015. Our research consists of an analytical, observational, cohort-based and retrospective study, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Meningiomas makes up about one third of all primary central nervous system tumours, being the most common brain tumour in adults over the age of 35 (1), with an incidence that has increased in recent years (2,3). As far as Romania is concerned, an increase in the number of intracranial meningiomas was noted in its North-Eastern region (where this research was conducted) over the 1990-2015 period (4). Although meningiomas are usually benign slow-growing tumours, their histological aggressiveness may classify them in grade II or III tumours, according to the WHO classification (5,6).…”
Section: Introductionmentioning
confidence: 84%
“…Meningiomas makes up about one third of all primary central nervous system tumours, being the most common brain tumour in adults over the age of 35 (1), with an incidence that has increased in recent years (2,3). As far as Romania is concerned, an increase in the number of intracranial meningiomas was noted in its North-Eastern region (where this research was conducted) over the 1990-2015 period (4). Although meningiomas are usually benign slow-growing tumours, their histological aggressiveness may classify them in grade II or III tumours, according to the WHO classification (5,6).…”
Section: Introductionmentioning
confidence: 84%
“…Meningiomas account for approximately one third of all intracranial tumors, being the most common primary intracranial neoplasm [ 1 ] and some of our previous studies have shown an increasing incidence and that these tumors are relative common in the north-eastern region of Romania [ 2 , 3 , 4 , 5 ].…”
Section: ⧉ Introductionmentioning
confidence: 99%
“…Meningiomas are the most common primary intracranial tumors in adults and represent about one third of them (26). Out of the histopathological grades of meningiomas, AMs (WHO grade II meningiomas) represent approximately 20-30% of them (27,28,33), and their incidence has increased in the last years (10,33).…”
Section: Introductionmentioning
confidence: 99%